Analisis Yuridis Status Tanah Tumbuh Di Kelurahan Kesenden Kecamatan Kejaksan Kota Cirebon - Berlian Phinisya Putri; Bambang Eko Turisno (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractChannel Bar is land that is formed due to Natural Factors and Human Actions, which is caused by sedimentation and forms sediment on the shore or on the riverbank. The issue of Channel Bar Status, is an important matter because it involves Legal Certainty. The objectives of this Research, namely How is the Status of the Channel Bar on the Edge of the Sea Shore, Kesenden Village, Kejaksan District, Cirebon City. Because, even though the National Land Law is realized, Customary Law is still complementary to the basis of the National Land Law itself. So that legal certainty is needed regarding the status of the growing land, so that there is legal certainty if in the future a legal action will be carried out between a legal subject and a growing land in the form of a legal object, especially in Kelurahan Kesenden, District Prosecutor's Office, Cirebon City.Keywords: channel bar status; land law; kesenden villageAbstrakTanah Tumbuh adalah Tanah yang terbentuk karena Faktor Alam dan Perbuatan Manusia, yang diakibatkan adanya sedimentasi dan membentuk endapan di pinggir pantai maupun di pinggir sungai. Masalah Status Tanah Tumbuh, merupakan salah satu hal yang penting karena menyangkut Kepastian Hukumnya. Tujuan dalam Penelitian ini, yaitu Bagaimana Status Tanah Tumbuh di Pinggiran Bantaran Laut Kelurahan Kesenden Kecamatan Kejaksan Kota Cirebon. Karena, walaupun terwujudnya Hukum Tanah Nasional, namun Hukum Adat tetaplah sebagai pelengkap dari dasar Hukum Tanah Nasional itu sendiri. Sehingga dibutuhkan Kepastian Hukum mengenai Status Tanah Tumbuh, agar adanya Kepastian Hukum jika nanti di kemudian hari akan dilakukan suatu Perbuatan Hukum antara Subjek Hukum dan Tanah Tumbuh yang berupa Objek Hukum, khususnya di Kelurahan Kesenden, Kecamatan Kejaksan, Kota Cirebon.Kata kunci: status tanah tumbuh; hukum tanah; kelurahan kesenden